Processamento sequencial de endocarpo de Butia capitata por meio de hidrólise com água subcrítica e liquefação hidrotérmica para obtenção de derivados líquidos e sólidos - Cunha, Henrique Nunes da (2022)
Butia capitata endocarp has potential to processing into wide variety of products. The processing of this biomass by environmentally friendly technologies such as subcritical water hydrolysis and hydrothermal liquefaction in the same equipment and in the same experimental run was investigated. For subcritical water hydrolysis, temperatures of 230 and 260 °C and solvent/feed ratios of 10 and 20 were evaluated in relation to yield in fermentable sugars and platform chemicals. For hydrothermal liquefaction, the effect of temperatures of 330 and 360 °C and the processing strategy, with or without subcritical water hydrolysis prior to hydrothermal liquefaction, on the yield of biocrudeoil and biochar were studied. The highest yields of fermentable sugars (5.26 ± 0.31 g/100 g Butia capitata endocarp) were obtained by subcritical water hydrolysis at 260 °C and solvent/feed ratio of 20. For the hydrothermal liquefaction process, there was the highest yield of biocrude oil (25.30 ± 2.13 g/100g Butia capitata endocarp) using liquefaction in a single step at 360 °C and solvent/feed ratio of 20.